2017
DOI: 10.1371/journal.pone.0188389
|View full text |Cite
|
Sign up to set email alerts
|

Growth, ammonium metabolism, and photosynthetic properties of Ulva australis (Chlorophyta) under decreasing pH and ammonium enrichment

Abstract: The responses of macroalgae to ocean acidification could be altered by availability of macronutrients, such as ammonium (NH4+). This study determined how the opportunistic macroalga, Ulva australis responded to simultaneous changes in decreasing pH and NH4+ enrichment. This was investigated in a week-long growth experiment across a range of predicted future pHs with ambient and enriched NH4+ treatments followed by measurements of relative growth rates (RGR), NH4+ uptake rates and pools, total chlorophyll, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 58 publications
(64 reference statements)
2
11
0
Order By: Relevance
“…References: [1] Ho and Carpenter (); [2] Sarker, Bartsch, Olischläger, Gutow, and Wiencke (); [3] Israel and Hophy (); [4] Gao et al (); [5] Lignell and Pedersén (); [6] García‐Sánchez et al (); [7] Rivers and Peckol (); [8] Chen, Zou, Zhu, and Yang (); [9] Xu, Zou, and Gao (); [10] Liu, Zou, and Yang (); [11] Zou and Gao (); [12] Kang, Kambey, Shen, Yang, and Chung (); [13] Kim et al (); [14] Suárez‐Álvarez, Gómez‐Pinchetti, and García‐Reina (); [15] Bender‐Champ, Diaz‐Pulido, and Dove (); [16] Kübler et al (); [17] Olischläger and Wiencke (); [18] Nunes et al (); [19] Sebök, Herppich, and Hanelt (); [20] Gordillo, Carmona, Viñegla, Wiencke, and Jiménez (); [21] Kram et al (); [22] Israel, Katz, Dubinsky, Merrill, and Friedlander (); [23] Liu and Zou (); [24] Xu, Chen, et al (); [25] Mercado, Javier, Gordillo, Xavier Niell, and Figueroa (); [26] Gao et al (); [27] de Paula Silva, Paul, Nys, and Mata (); [28] Reidenbach et al (); [29] Kang and Chung (); [30] Kang and Kim (); [31] Liu and Zou (); [32] Gao et al (); [33] Xu and Gao (); [34] Li, Xu, and He (); [35] Li, Zhong, Zheng, Zhuo, and Xu (); [36] Björk, Haglund, Ramazanov, and Pedersén (); [37] Gordillo, Niell, and Figueroa (); [38] Rautenberger et al (); [39] Gordillo, Figueroa, and Niell (); [40] Iñiguez et al (); [41] Gordillo et al (); [42] Iñiguez, Heinrich, Harms, and Gordillo (); [43] Gutow et al (); [44] Kawamitsu and Boyer (); [45] Ober and Thornber (); [46] Mensch et al (); [47] Iñiguez et al, (); [48] Fernández et al (); [49] Swanson and Fox (); [50] Thom (); [51] Kang and Chung (); [52] Olischläger, Iñiguez, Koch, Wiencke, and Gordillo (); [53] Zou (); [54] Zo...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…References: [1] Ho and Carpenter (); [2] Sarker, Bartsch, Olischläger, Gutow, and Wiencke (); [3] Israel and Hophy (); [4] Gao et al (); [5] Lignell and Pedersén (); [6] García‐Sánchez et al (); [7] Rivers and Peckol (); [8] Chen, Zou, Zhu, and Yang (); [9] Xu, Zou, and Gao (); [10] Liu, Zou, and Yang (); [11] Zou and Gao (); [12] Kang, Kambey, Shen, Yang, and Chung (); [13] Kim et al (); [14] Suárez‐Álvarez, Gómez‐Pinchetti, and García‐Reina (); [15] Bender‐Champ, Diaz‐Pulido, and Dove (); [16] Kübler et al (); [17] Olischläger and Wiencke (); [18] Nunes et al (); [19] Sebök, Herppich, and Hanelt (); [20] Gordillo, Carmona, Viñegla, Wiencke, and Jiménez (); [21] Kram et al (); [22] Israel, Katz, Dubinsky, Merrill, and Friedlander (); [23] Liu and Zou (); [24] Xu, Chen, et al (); [25] Mercado, Javier, Gordillo, Xavier Niell, and Figueroa (); [26] Gao et al (); [27] de Paula Silva, Paul, Nys, and Mata (); [28] Reidenbach et al (); [29] Kang and Chung (); [30] Kang and Kim (); [31] Liu and Zou (); [32] Gao et al (); [33] Xu and Gao (); [34] Li, Xu, and He (); [35] Li, Zhong, Zheng, Zhuo, and Xu (); [36] Björk, Haglund, Ramazanov, and Pedersén (); [37] Gordillo, Niell, and Figueroa (); [38] Rautenberger et al (); [39] Gordillo, Figueroa, and Niell (); [40] Iñiguez et al (); [41] Gordillo et al (); [42] Iñiguez, Heinrich, Harms, and Gordillo (); [43] Gutow et al (); [44] Kawamitsu and Boyer (); [45] Ober and Thornber (); [46] Mensch et al (); [47] Iñiguez et al, (); [48] Fernández et al (); [49] Swanson and Fox (); [50] Thom (); [51] Kang and Chung (); [52] Olischläger, Iñiguez, Koch, Wiencke, and Gordillo (); [53] Zou (); [54] Zo...…”
Section: Resultsmentioning
confidence: 99%
“…Target CO 2 levels were achieved in each of the 24 culture containers using a system similar to that described in Bockmon, Frieder, Navarro, White‐Kershek, and Dickson () with the modifications presented in Reidenbach et al (). Briefly, every 4 hr, seawater in each 650‐ml culture container was replaced by flushing the container with ~1 L of seawater using Jebao DP‐4 Auto Dosing aquarium pumps.…”
Section: Methodsmentioning
confidence: 99%
“…For example, OA has a positive influences on the growth of macroalgae, such as the red algae Pyropia yezoensis, Pyropia haitanensis and Gracilaria lemaneiformis (Gao et al, 1991;Xu & Gao, 2015;Chen et al, 2018), green algae Ulva prolifera, Ulva lactuca, Caulerpa taxifolia Chen et al, 2015;Roth-Schulze et al, 2018) and brown algae Hizikia fusiforme, Ecklonia radiata, Sargassum muticum (Zou, 2005;Britton et al, 2016;Xu et al, 2017). However, research has shown that high CO 2 levels did not have a detectable effect on the relative growth rate of several species, for example, Sargassum henslowianum, Ulva rigida, Ulva australis, the giant kelp Macrocystis pyrifera and Ulva australis (Chen & Zou, 2014;Rautenberger et al, 2015;Fernández et al, 2015;Reidenbach et al, 2017). Furthermore, increasing seawater CO 2 concentration reduced the growth of Gracilaria tenuistipitata, Porphyra leucosticte, Fucus vesiculosus, Halimeda opuntia and Ulva linza (García-Sánchez et al, 1994;Mercado et al, 1999;Gutow et al, 2014;Johnson et al, 2014;Gao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For diatoms, this energetic bonus of downregulation has been estimated to be too small to account for positive effects of OA on growth rate (Kranz et al 2015;Young et al 2015). Enhancement of growth rates and/or photosynthetic rates under OA could be due to other factors, such as changes in efficiency of nutrient uptake (Young and Gobler 2016;Kang and Chung 2017;Reidenbach et al 2017) or, at the ecosystem level, species biomass composition. Another reason for uncertainty is that the positive effects of OA that are expected for productivity of strictly CO 2 -using phototrophs that are carbon-limited at present appear small (Kübler and Dudgeon 2015).…”
mentioning
confidence: 99%
“…Finally, recent experimental studies of macroalgae and seagrasses show highly variable effects of OA on photosynthetic metabolism (Xu and Gao 2012;Fernandez et al 2015;Gao et al 2016Gao et al , 2018Young and Gobler 2016;Reidenbach et al 2017;Xu et al 2017;Legrand et al 2018). Much of the variability between strong, weak, or null effects may be due to the different experimental conditions used, species studied, and their environmental histories prior to sampling.…”
mentioning
confidence: 99%